Epidemiology of persistent postoperative opioid use after cardiac surgery: a systematic review and meta-analysis. (September 2022) - Liu, Zhengyang; Karamesinis, Alexandra D.; Plummer, Mark; Segal, Reny; Bellomo, Rinaldo; Smith, Julian A.; Perry, Luke A.
Abstract: Background: The epidemiology of persistent postoperative opioid use at least 3 months after cardiac surgery is poorly characterised despite its potential public health importance. Methods: We searched MEDLINE, Embase, and Google Scholar from inception to December 2021 and included studies reporting the rate and risk factors of persistent postoperative opioid use after cardiac surgery in opioid-naive and opioid-exposed patients. We recorded incidence rates and odds ratios (ORs) with 95% confidence intervals (CIs) for risk factors from individual studies and used random-effects inverse variance modelling to generate pooled estimates. Results: From 10 studies involving 112 298 patients, the pooled rate of persistent postoperative opioid use in opioid-naive patients was 5.7% (95% CI: 4.2–7.2%). Risk factors included female sex (OR 1.18; 95% CI: 1.09–1.29), smoking (OR 1.34; 95% CI: 1.06–1.69), alcohol use (OR 1.43; 95% CI: 1.17–1.76), congestive cardiac failure (OR 1.17; 95% CI: 1.08–1.27), diabetes mellitus (OR 1.21; 95% CI: 1.07–1.37), chronic lung disease (OR 1.42; 95% CI: 1.16–1.75), chronic kidney disease (OR 1.35; 95% CI: 1.08–1.68), and length of hospital stay (per day) (OR 1.03; 95% CI: 1.02–1.04). Conclusions: Persistent postoperative opioid use after cardiac surgery affects at least one in 20 patients. The identification of risk factors, such as female sex, smoking, alcohol use, congestive cardiac failure, diabetes mellitus, chronic lung disease, chronic kidney disease, and length of hospital stay, should help target interventions aimed at decreasing its prevalence.